Untargeted Safety Pharmacology Screen of Blood-Activating and Stasis-Removing Patent Chinese Herbal Medicines Identified Nonherbal Ingredients as a Cause of Organ Damage in Experimental Models - Liu, Xinyan; Shao, Rui; Yang, Xinyue; Xiao, Guangxu; He, Shuang; Feng, Yuxin; Zhu, Yan (Frontiers in Pharmacology, 2019)
Blood-activating and stasis-removing medicines (BASRMs)is a widely prescribed chinese patent medicines for cerebral and cardiovascular diseases in China. However, its safety effects on body and the underlying mechanisms remain unknown. Taking an integrated approach of tissue level and cell level analysis, we compared morphological characteristics of tissue to screen for toxic characteristics by H9C2 cells,HepG2 cells and HEK293 cells.In the animal experiment, Adriamycin was injected intraperitoneally with 2.5 mg / ml as a positive drug.Naoluotong capsule (NLTC) at 7.8mg and 39mg/20g by gavage. Besides, NLTC at 7.8mg and 39mg/20g also markedely reduced the levels of crea in serum. Chemical analysis by HPLC revealed that the topperidone hydrochloride has a tenth of the total drug, methyl hesperidin has 1/50,vitamin B6 has 1/250. The 3 chemical monomers were evaluated for activity at the cellular level.In conclusion, our study showed that the chinese patent medicine composed of chinese herbal medicines of BASRMs is safer than the chinese and western compound preparations, and the toxicity of the chinese and western compound preparations may mainly come from the chemical monomer tolperisone hydrochloride.Patients who used chinese and western compound preparations should take rational medicine under the guidance of doctors, pay attention to the dosage and avoid adverse reactions .NLTC side effect mechanism need further study.